Upper airway stimulation for obstructive sleep apnea: patient-reported outcomes after 48 months of follow-up - Gillespie, M. Boyd; Maurer, Joachim T. (Head and neck surgery, 2017)
ObjectiveTo assess patient-based outcomes of participants in a large cohort study?the STAR trial (Stimulation Therapy for Apnea Reduction)?48 months after implantation with an upper airway stimulation system for moderate to severe obstructive sleep apnea.Study DesignA multicenter prospective cohort study.SettingIndustry-supported multicenter academic and clinical setting.SubjectsParticipants (n = 91) at 48 months from a cohort of 126 implanted participants.MethodsA total of 126 participants received an implanted upper airway stimulation system in a prospective phase III trial. Patient-reported outcomes at 48 months, including Epworth Sleepiness Scale (ESS), Functional Outcomes of Sleep Questionnaire (FOSQ), and snoring level, were compared with preimplantation baseline.ResultsA total of 91 subjects completed the 48-month visit. Daytime sleepiness as measured by ESS was significantly reduced (P = .01), and sleep-related quality of life as measured by FOSQ significantly improved (P = .01) when compared with baseline. Soft to no snoring was reported by 85% of bed partners. Two patients required additional surgery without complication for lead malfunction.ConclusionUpper airway stimulation maintained a sustained benefit on patient-reported outcomes (ESS, FOSQ, snoring) at 48 months in select patients with moderate to severe obstructive sleep apnea.
Article first published online: February 14, 2017
Gesehen am 27.06.2018
This article was presented at the 2016 AAO-HNSF Annual Meeting & OTOEXPO; September 18-21, 2016; San Diego, California